2011
DOI: 10.1016/j.pain.2011.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of acupuncture for migraine prophylaxis: A single-blinded, double-dummy, randomized controlled trial

Abstract: Insufficient clinical trial data were available to prove the efficacy of acupuncture for migraine prophylaxis. A multicenter, double-dummy, single-blinded, randomized controlled clinical trial was conducted at the outpatient departments of acupuncture at 5 hospitals in China to evaluate the effectiveness of acupuncture. A total of 140 patients with migraine without aura were recruited and assigned randomly to 2 different groups: the acupuncture group treated with verum acupuncture plus placebo and the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 29 publications
6
88
0
Order By: Relevance
“…As shown in Figure 3, EA at GB20 produced a decrease in resting, freezing, and grooming behaviors, and an increase in exploration behavior in migraine rats. EA pretreatment decreases the dural electrical stimulations-evoked response without reaching response values in the Control group, and this finding is similar to that demonstrated in migraineurs [11, 31, 32], in which acupuncture is not completely effective but helps to diminish pain during migraine attacks.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As shown in Figure 3, EA at GB20 produced a decrease in resting, freezing, and grooming behaviors, and an increase in exploration behavior in migraine rats. EA pretreatment decreases the dural electrical stimulations-evoked response without reaching response values in the Control group, and this finding is similar to that demonstrated in migraineurs [11, 31, 32], in which acupuncture is not completely effective but helps to diminish pain during migraine attacks.…”
Section: Discussionsupporting
confidence: 86%
“…The rats were placed into a tailored apparatus that exposed their heads and necks sufficiently. GB20 is a commonly used acupuncture point for treating migraines [11]. In rats, the point is anatomically similar to that in humans, as it is located 3 mm lateral to the center of a line joining the two ears at the back of the head.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty studies (described in 23 publications) did not meet selection criteria (Agro 2005; Boutouyrie 2010; Ceccherelli 2012; Deng 2006; Ferro 2012; Foroughipour 2014; Han 2011; Jia 2009; Matra 2012; Qin 2006; Vijayalakshmi 2014; Wang 2011; Wu 2011; Yang 2009; Yang 2011; Zhang 2006; Zhang 2009; Zheng 2013; Zhong 2009; Zhou 2007). A number of Chinese trials were excluded due to inadequate duration of prophylactic drug treatment (several Chinese trials gave flunarizine or other drugs for four weeks only), overall observation of less than eight weeks, inclusion of participants with recent onset of migraine, and lack of relevant outcome measures.…”
Section: Resultsmentioning
confidence: 99%
“…The latest Cochrane meta-analysis suggests that acupuncture as a migraine prophylaxis is safe and at least as effective, if not more effective, than prophylactic drug treatment [10]. During the past decade, a considerable number of high quality clinical studies have indicated that acupuncture is able to alleviate headache degree and/or improve the QOL [11][13]. However, despite the popularity of acupuncture in migraine therapy, there persists limited knowledge on the physiological mechanisms behind this method, and some controversy on the superiority of verum acupuncture over sham control.…”
Section: Introductionmentioning
confidence: 99%